Sequencing and Annotated of Goat’s Milk Using Bioinformatics Tool: ClustalX - Muhammad Najmi Mohammad Fauzi; Aisyah Aqilah Abu Bakar; Liyana Amalina Adnan; Tg Ainul Farha Tg Abdul Rahman; Nurdalila A’wani Abdul Aziz (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology